Estudo comparativo da estabilidade térmica e oxidativa do óleo de moringa (Moringa oleifera L.) com óleos comestíveis convencionais - Oliveira, Andreza Moraes Duarte de (2018)
In the search of more stable oils to use in the frying process, this research investigates the thermo-oxidative stability of Moringa oil – Sourced from the Moringa seed- compared with conventional oils such as Olive oil, Canola, and Soybean oil. The oils were characterized by their acidity level, iodine, saponification and their peroxides, as well as their kinematic viscosity and fatty acids content. The following testing methods were used to analyze thermooxidative stability. The Rancimat, PetroOXy, Schaal and thermogravimetry tests. Each to analyze the reaction of the oil when frying meat, (steak), fish (sardine) and potatoes. This testing employed the use of Infrared Spectroscopic and Nuclear Magnetic Resonance of Hydrogen (RMN 1H). The Moringa oil was equal to the Olive, Canola and the Soybean oil. Demonstrating acidity and peroxide levels that are in compliance with Brazilian law. Regarding the iodine value, saponification and viscosity, the moringa oil was similar to Olive oil. This was in contrast to the Canola and Soybean oils where the results were dissimilar. The results of the Thermo-Oxidative analysis, accounting for differing accelerated oxidation methods, showed that the Moringa oil was more stable than the others. In the Schaal Test the Moringa oil isomerization of the double bonds was similar to that of Extra Virgin Olive Oil, yet less than the Canola and Soybean oils. The examination of the frying process using the RMN 1H method, showed that Moringa oil presented less oxidation by-products when frying the meat and potatoes. During the fish frying process there was no formation of any byproducts. Yet, interestingly, it was observed that an omega 3 migrated from the fish to the oil. The group of results obtained showed that the Moringa oil had an oxidative and thermo stability similar to that of Olive oil. This would indicate a greater shelf life when compared to the other oils in this research. Considering its thermo oxidative conduct during the frying tests, it proved it appeared most suited for this purpose. This stands in contrast to the Canola oil and Soybean oil.